PENGGUNAAN PUPUK KOMPOS AKTIF Trichoderma sp DALAM MENINGKATKAN PRODUKSI TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Jostefin Tigahari; Bertje Sumayku; Maria Polii (Universitas Sam Ratulangi, 2020)
ABSTRACTCayenne pepper (Capsicum frutescens L.) is a fruit vegetable, which is needed by all levels ofsociety, because apart from being a spice for cooking and medicinal plants it is also a source oflivelihood. Environmental factors that have the potential to influence the development and yield ofchili plants include the high rainfall that is unpredictable throughout the year. The results of severalstudies indicate that the active compost of Trichoderma sp. can help growth and good results forplants. Trichoderma sp. is one of the biological control agents that have been widely used to controlplant pathogenic microbes. This research aims to study the growth and production of chili plants fedwith active compost Trichoderma sp. This research has been carried out at the Kalasey Center forFood Crops and Horticulture in North Sulawesi for 3 months from March to June 2018. The tools tobe used are: hoes, shovels, ropes, sticks, scales, sacks, writing instruments and cameras. Materialsto be used are: Nirmala's cayenne pepper seeds, soil, water, polybags, active compost Trichodermasp. and label paper. The research design was arranged in a randomized block design (RBD) with 6treatments repeated 3 times. Trichoderma sp. Active compost dosage treatment are: T0 = withoutactive compost treatment Trichoderma sp. T1 = active compost of Trichoderma sp. 50 g / 10 kg ofsoil T2 = active compost of Trichoderma sp. 100 g / 10 kg soil T3 = active compost of Trichodermasp. 150 g / 10 kg soil T4 = active compost of Trichoderma sp. 200 g / 10 kg of soil T5 = activecompost Trichoderma sp. 250 g / 10 kg of soil. Each treatment used 6 polybags with each polybagcontaining one plant. So the total number of polybags is 108 polybags. Data were analyzed usingAnalysis of Variance (Anova) to see the effect of treatment. If the treatment shows a significanteffect, the analysis is continued using the 5% LSD test. Based on the results obtained in thisexperiment, it can be concluded that the application of active compost Trichoderma sp 250 gramshas the best effect on plant height, number of leaves, flowering time, number of fruits, wet fruitweight and production of cayenne pepper.